Intensive reading skills with cooperative integrated reading composition (CIRC) and group investigation (GI) - Ika Panggih Wahyuningtyas; Ermanto Ermanto; Abdurahman Abdurahman (Fakultas Ilmu Pendidikan UNP)
This research aims to know the difference in the results of learning to read with intensive using the model of the CIRC and learning motivation of GI in grade VII MTs Country Muara Bulian. This type of research was quasi experiment (experiment of the artificial) and design used in this study is a 2 x 2 factorial. This research population is students of Class VII MTs Country Muara Bulian. First, The average reading skills of students who are taught in an intensive learning CIRC. was 81.00, while students taught with model GI was 79.40. Both , the average the learning model CIRC. is 83.25, students learning motivation high taught with model GI was 84.40. Third, the average reading skills of students ' learning motivation low intensive taught by learning model CIRC. was 78.75 and taught with model GI is 74.40.